2010
DOI: 10.1007/s11671-010-9615-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ZnGa2O4 Hierarchical Nanostructure by Au Catalysts Induced Thermal Evaporation

Abstract: In this paper, ZnGa2O4 hierarchical nanostructures with comb-like morphology are fabricated by a simple two-step chemical vapor deposition (CVD) method: first, the Ga2O3 nanowires were synthesized and employed as templates for the growth of ZnGa2O4 nanocombs; then, the as-prepared Ga2O3 nanowires were reacted with ZnO vapor to form ZnGa2O4 nanocombs. Before the reaction, the Au nanoparticles were deposited on the surfaces of Ga2O3 nanowires and used as catalysts to control the teeth growth of ZnGa2O4 nanocombs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…These CL results are different from those in the Chang and Wu study where they observed a strong emission at 360 nm and a weak emission at 680 nm [6]. However, our results are in good agreement with those of X M Chen et al [11]. Thus, the emission peak at around 450 nm in the ZnGa 2 O 4 spectrum can be attributed to the self-activated centers originating from the octahedral Ga-O group in the normal lattice of ZnGa 2 O 4 .…”
Section: Luminescence Studycontrasting
confidence: 65%
See 1 more Smart Citation
“…These CL results are different from those in the Chang and Wu study where they observed a strong emission at 360 nm and a weak emission at 680 nm [6]. However, our results are in good agreement with those of X M Chen et al [11]. Thus, the emission peak at around 450 nm in the ZnGa 2 O 4 spectrum can be attributed to the self-activated centers originating from the octahedral Ga-O group in the normal lattice of ZnGa 2 O 4 .…”
Section: Luminescence Studycontrasting
confidence: 65%
“…Thereafter, Chang and Wu fabricated ZnGa 2 O 4 NWs via a two-step method including chemical vapor deposition (CVD) and metal-organic CVD (MOCVD) techniques [6]. Recently, Chen et al prepared ZnGa 2 O 4 hierarchical nanostructures using a single route process [11]. In spite of these studies, an extensive growth study of ZnGa 2 O 4 NWs using a double route process along with their structural, morphological and optical characterization is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…ZnGa 2 O 4 structures have been prepared by a lot of methods, including the hydrothermal method, chemical vapour deposition, thermal evaporation, and so on [16][17][18][19]. Among these methods, hydrothermal method is one of the most promising solution methods.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of cost-effective and scalable growth of MGa 2 O 4 1D arrays has limited their practical applications. Disordered ensembles of ZnGa 2 O 4 NWs were previously synthesized by high-temperature (∼1000 °C) vapor reactions via the VLS growth using Au nanoparticle catalysts. Such vapor growth suffers from the high cost and difficulty in compositional control. Another seemingly inconspicuous but practically important drawback is that such high temperatures greatly limit the choice of substrates, because commonly used substrates, such as FTO coated glass, cannot tolerate temperatures higher than 600 °C.…”
mentioning
confidence: 99%